Sistem Monitoring Beban Tiga Fasa pada Gardu Distribusi berbasis Internet of Things - Tandepadang, Eklesia Anggara; Jabbar, A. Abd. (Jurnal Mosfet, 2024)
To achieve optimal results in distributing electrical loads, maintaining load balance among phases in a three phase installation system is essential, as any imbalance can lead to electrical power losses. One of the factors contributing to load imbalances is the improper installation of electrical equipment across the phases, deviating from the existing installation design. This research aims to develop a system, known as the Load Monitoring System, capable of storing and providing information about the load conditions installed on a three-phase transformer loading system. This system aims to facilitate the process of adding customers, dividing the load on each phase, avoiding load imbalances, and serving as a reference for routine maintenance of distribution substations annually. The methodology employed in this research is a quantitative method based on testing Internet of Things (IoT) monitoring system tools. The results show that the system effectively monitors load current and voltage at the distribution substation. Additionally, the device enables remote monitoring with the Transmitter capable of sending data to the Receiver from distances ranging from 50 m to 100 m and with the TX Max position in dense environmental conditions and full of obstacles such as buildings and trees or in rural areas with limited internet connectivity.